PENGARUH SKOR GOOD CORPORATE GOVERNANCE TERHADAP PERLUASAN PENGUNGKAPAN SUKARELA SYARIAH - Ratih Milati Ilham; Fithri Widyanita Yarisma; Chadyan Fathurachman (LPPM Universitas Bina Bangsa, 2024)
This study aims to examine whether there is an influence of good corporate governance score on extend of voluntary shari’a disclosure. The population in this study were companies listed on the Indonesia Stock Exchange. The number of samples in this study were 22 companies. The sampling technique uses purposive sampling method. The research method used is quantitative with secondary data sources. The methode of data analysis uses multiple linear regression analysis with SPSS version 25. The results of this study provide evidence that the good corporate governance score variable has no effect on the expansion of voluntary disclosure